2022
DOI: 10.4103/atm.atm_495_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radial endobronchial ultrasound-guided transbronchial lung biopsy with distance measurement versus with guide sheath in diagnosing peripheral pulmonary lesions with a diameter ≥3 cm by thin bronchoscope

Abstract: OBJECTIVE: This study aims to explore the diagnostic values of radial endobronchial ultrasound-guided transbronchial lung biopsy with distance (rEBUS-D-TBLB) measurement and with guide sheath (rEBUS-GS-TBLB) for peripheral pulmonary lesions (PPLs) with a diameter ≥3 cm by thin bronchoscope. PATIENTS AND METHODS: Six hundred and three patients with PPL (diameter ≥3 cm) were enrolled in this study. The subjects were divided into the rEBUS-D-TBLB and rEBUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…On strati cation, Oki et al (24) suggested the GS group was better with peripheral lesions (53.4% vs. 43.8%, p = 0.032) and positive bronchus signs on CT (59.2% vs. 49.1%, p = 0.029); while in Guan's study, (25) the GS group was also better with peripheral lesions (76.30% vs. 74.59%), but worse with central lesions (72.37% vs. 81.44%). Other studies also proposed that the GS was better with peripheral, small lesions, as well as concentric lesions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…On strati cation, Oki et al (24) suggested the GS group was better with peripheral lesions (53.4% vs. 43.8%, p = 0.032) and positive bronchus signs on CT (59.2% vs. 49.1%, p = 0.029); while in Guan's study, (25) the GS group was also better with peripheral lesions (76.30% vs. 74.59%), but worse with central lesions (72.37% vs. 81.44%). Other studies also proposed that the GS was better with peripheral, small lesions, as well as concentric lesions.…”
Section: Discussionmentioning
confidence: 88%
“…The diagnostic yield was 55.3% versus 46.6% (GS vs. non-GS; p = 0.033). However, the study from Guan et al (25) suggested the non-GS had a higher diagnostic yield. They included 569 cases with PPLs ≥ 30 mm in diameter, and the positive diagnosis rate was 74.91% vs. 76.95% (GS vs. non-GS; non-inferiority U-test p ≤ 0.05).…”
Section: Discussionmentioning
confidence: 96%